The Effect of Installing Modified Copper in Muffler to Reduce CO Levels in Vehicle Exhaust - Nugroho, Arif Setyo (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
This study aims to determine the effectiveness of modified copper to reduce carbon monoxide (CO) levels. Copper in the form of a plate shaped like a honeycomb and altered with activated carbon (SiO) and ZSM-5. The test uses a four-stroke 125 CC two-wheeled motor vehicle, fuel using Petalite, gasohol E5, gasohol E10, gasohol E15. The test carried out is the emission test of the effect of fuel variations and modified copper. The use of petalite fuel, variations of honeycomb copper + activated carbon (SiO-C) + ZSM-5 is more effective because it can reduce CO levels the most, which is 3.66% CO at 9000 rpm engine speed. For E5 fuel, the use of a honeycomb-shaped copper exhaust + Titan dioxide (TiO2) + Activated carbon (SiO-C) + ZSM-5 reduces CO levels by 3.42% CO at 9000 rpm engine speed. On the other hand, E10 fuel reduces CO levels by 1.35% CO when using exhaust with honeycomb copper+ TiO2 + SiO-C +ZSM-5.